Etiological Aspects of Infectious Endocarditis in a Tertiary Hospital in Northeastern Romania - Isabela Ioana Loghin; Amelia Elena Surdu; Șerban Alin Rusu; Ion Cecan; Victor Daniel Dorobăț; Amelia Andreea Mihăescu; Carmen Mihaela Dorobăţ (Medicina)
Background and Objectives: Infective endocarditis (IE) is a severe, life-threatening infection of the endocardial surface. Its incidence has shifted towards older, immunocompromised patients and those with cardiac devices. Materials and Methods: This study was conducted at the “Sf. Parascheva” Clinical Hospital of Infectious Diseases in Iasi, Romania, and retrospectively analyzed cases of IE from January 1, 2019, to September 30, 2024. It received ethical approval (Approval No. 7/17 June 2024). Results: The study included 130 patients with infectious endocarditis, predominantly men (75.38%), with a median age of 55 years. The most affected age groups were 50–59 and over 60 years, each representing 30.76% of cases. The most frequently implicated etiological agent was Staphylococcus aureus in 33% of cases. The most common antibiotic regimen combined glycopeptides and fluoroquinolones/polymyxins (27% cases). Conclusions: A multidisciplinary approach involving infectious disease specialists, cardiologists, and cardiovascular surgeons is essential for effective treatment. Immediate combined antibiotic therapy is vital for presumed IE cases. Despite advances in diagnosis and treatment, the high mortality rates highlight the importance of timely intervention. Future research should focus on improving preventive and therapeutic strategies for IE.